Performance of slab-column connections of flat slabs strengthened with carbon fiber reinforced polymers. (December 2019) - Silva, M.A.L.; Gamage, J.C.P.H.; Fawzia, S.
Abstract: Retrofitting of slab-column connections has become a crucial concern as they are highly vulnerable to fail in punching shear failure. External strengthening is practically feasible rather than the post-installation of shear reinforcement in deteriorated slab-column connections. Hence, the behavior of medium scale slab-column junctions strengthened with alternative arrangements of Carbon Fiber Reinforced Polymer (CFRP) was studied. Numerical models were also developed to analyze bond behavior. The model predicted performances are in good agreement with the test results. The maximum average punching shear enhancement of 46% was observed from the specimens with CFRP plates attached to the tension face of the specimens with steel end anchors.